The Historical Background of the Definition of Barbarism and its Occurrence in The Literary Texts - Sobirova Zarnigor Rakhimovna (Indonesian Journal of Innovation Studies, 2022)
The article defines the word barbarism and its historical etymology. It studies its occurrence in the poetry and literature of the world.